Imagen fotográfica del tiempo: la obra de Plossu y de Iasparra - Magnetto, Vanesa (2018)
This paper develops around the representation and construction of time in the photographic image. We propose two axes of analysis (technical and spatial) to visit the collection of pictures, composed by El Jardín de Bernard, by Bernard Plossu, and Paisajes, by Ignacio Iasparra. The problem proposed by this paper should be seen as the potential of Time in these pictures for resisting the hegemonic photographic language, governed by a present, instantaneous image, in close dialogue with contemporary global time and the capitalist system.